Measuring The Impact of Agricultural Insurance on The Sustainability of Agricultural Production Under Climate Change in Algeria (2002-2022) - Tamini , Maroua; Ameur , Oussama; Lagoune , Salim (Dirassat Journal Economic Issue, 2025)
This research paper aims to analyze the impact of agricultural insurance on the volume of agricultural production and its role in mitigating climate change in Algeria during the period 2002-2022. Using annual data on the volume of agricultural production as a dependent variable, and the annual average temperature and agricultural insurance premiums as independent variables, the Autoregressive Distributed Lag (ARDL) model was applied. This research paper concluded that agricultural production has a long-term inverse relationship with its explanatory variables, due to the insufficiency of agricultural insurance to cover all climate risks if they occur, which led to an exacerbation of the negative impact of climate change, while a direct relationship was found between the model variables in the short term, reflecting the integration of temperature and agricultural insurance in providing a stable and stimulating environment for agricultural production. It was also shown that the correction coefficient is negative and significant, as the speed of adaptation to reach the equilibrium situation was estimated at 4 months and 18 days.